New Strategies towards Bulky Bis(alkyl)‐ and Bis(silyl)‐ Substituted Polysilanes as Precursor Molecules for Desilylation and Dechlorination Experiments. Issue 19 (6th May 2021) - Lainer, Thomas; Pillinger, Michael; Fischer, Roland C.; Jones, Cameron; Haas, Michael
Abstract: Herein we report on a series of bulky bis(alkyl)‐ and bis(silyl)‐ substituted polysilanes. Moreover, we performed desilylation and dechlorination experiments with them. These compounds were characterized by multinuclear NMR spectroscopy, mass spectrometry, and X‐ray crystallography. It was found that the selective formation of silyl mono‐ and di‐anions is crucial for the successful isolation of these polysilanes. Moreover, we utilized a multiple silyl abstraction methodology to obtain the spiro‐compounds 6 and 8 . The latter was tested as a precursor molecule for the synthesis of bis(silyl)silylenes. Abstract : New synthetic pathways towards a series of neutral bulky Bis(alkyl)‐ and Bis(silyl)‐ substituted polysilanes are described. Their reactivity was investigated by desilylation and dechlorination experiments. All isolated compounds were characterized by multinuclear NMR spectroscopy, mass spectrometry and X‐ray crystallography.